God’s gift : narratives of disability in Malay popular fiction - Ruzy Suliza Hashim; Mohd Muzhafar Idrus; Mary Ellen Gidah (Penerbit Universiti Kebangsaan Malaysia, 2022)
The synthesis of literature and popular culture helps literary scholars form inferences about the challenges preoccupying society's collective psyche. It is therefore no stretch to assert that popular fiction, particularly popular fiction that has garnered sufficient traction to be adapted into a popular telenovela with a sizable following, is reflective of the general public's perceptions on any given issue. Having garnered sufficient attention, it is then capable of influencing, to some extent, those same public perceptions. The malleability of public opinion in reaction to what is broadcast or written is a valuable instrument for comprehending cultural paradigms. It is important, then, to analyse telenovelas and the novels upon which they are based in order to put a metaphorical finger on Malaysian attitudes toward disability. This article will focus on two Malay books that have been converted into telenovelas with the same names due to their popularity. These novel-based perceptions will then be compared to real-world experiences of caregivers and family members of children with autism in order to demonstrate that, while autism may appear to be a life sentence, children with autism are also perceived as God’s gift. Additionally, while it is necessary to acknowledge how disability shapes our perceptions of what it means to be mocked for our insignificance and disability, the concepts of forgiveness and repentance appear the Malay worldview, with the implication that forgiving others' faults exemplifies a human virtue.